(untitled) (Argos, 2024)
The heroes who attend to the renowned journey to Colchis are preceded by an individual identity that coexists, during the expedition, with a collective Argonautical identification. This characterization as Minyans, which is unfolded along the epic, proposes to keep the harmony (ὁμόνοια) and solidarity within the group and prevents from anger (μῆνις) and arrogance, inter alia. There are two characters, nevertheless, that are presented in the catalogue as arrogant (ὑπέρβιος): Idas and Ancaeus. My aim in this article is to analyze how the Argonautical identity defines and in what way the tension between the singular identification of Idas and Ancaeus and the group qualities settled solves.